ANALISIS FAKTOR PENERIMAAN PAJAK PENGHASILAN DENGAN KEPATUHAN WAJIB PAJAK SEBAGAI VARIABEL INTERVENING - Irfan Irfan; M Firza Alpi (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the effect of the number of tax audits and tax sanctions on income tax revenues through taxpayer compliance as an intervening variable at KPP Pratama Medan Timur. This study uses primary data by conducting direct research in the field as many as 44 respondents through a questionnaire with a Likert scale. Statistical method used with Path Analysis. By using SPSS 26 program. Path analysis results found that: the number of tax audits has an effect on tax revenue, but tax sanctions have no partial effect. the number of tax audits and tax sanctions have a significant effect on taxpayer compliance. However, partially, only tax audits have a positive and significant effect on tax audits, tax sanctions and taxpayer compliance have a positive and significant effect on tax revenue at KPP Pratama Medan Timur, but partially only taxpayer compliance has a positive and significant effect. taxpayer compliance is able to mediate the effect of tax audits on taxpayers. However, it cannot mediate/intervening tax sanctions on tax revenues at KPP Pratama Medan Timur.